Strategic Human Resource Development & Support System Characteristics - Reza Hafidz Dwi Saputro (International Journal of Social Service and Research, 2023)
The concept of Strategic Human Resource Management has become a very important and interesting discussion at Polda Bali. A company if it wants to succeed in competition in the global era like today must be able to make a human resource management design that has the ability and is responsive to changes in the business world in the future (strategic). The research aims to explain the concept of strategic human resource management (HRMS) and the characteristics of its support system in an effort to contribute to company performance. This MSDMS research uses a qualitative approach by using a literature review in presenting theories about the research problems being conducted. This study concludes strategic human resource management (HRM) primarily from a process point of view to improve organizational performance. First, analyzing the common features in the definition of HRM clarifies five features (close fit between human resource management (HRM) and management strategy, etc.). Second, approaches that investigate the relationship between strategy, HR practices and organizational performance are reviewed. As a result, best practice approaches have been frequently used and produce comparatively useful results with contingency approaches and configurational approaches. The PSDM system will be considered to have strategic value in the context of public management reform only if it has the ability to develop a supportive environment for learning, where there is a clear link between the PSDM and the government's strategic objectives. national institutions, which in turn have been aligned with the goals of public management reform. Strategic PSDM is a prerequisite for an emerging learning culture and for learning organizations to thrive.